Pelatihan Pembuatan Bahan Ajar Berbasis Etnosains Jayapura Bagi Guru IPA di Distrik Muara Tami Kota Jayapura - Putu Victoria M. Risamasu; Jan Pieter (J-Abdimas Cenderawasih, 2026)
Community service activities have been carried out for Science Teachers at the MGMP IPA Muara Tami District Jayapura. This activity aims to (1) provide knowledge to science teachers about the inclusion of ethnoscience in the creation of teaching materials, (2) provide skills to science teachers in creating ethnoscience-based teaching materials, and (3) produce ethnoscience-based teaching material products Jayapura. Community service activities are carried out in the form of training with lecture methods, discussions and mentoring in the practice of making teaching materials. This service was carried out for 2 months from August-September 2025, involving 8 science teachers throughout the Muara Tami District which was centered at SMP Negeri 8 Jayapura. At the end of the community service activities, the Community Service team obtained the following results: a) Science teachers in Muara Tami Jayapura District have knowledge related to Ethnoscience that can be used in science learning in class, b) Science teachers in Muara Tami Jayapura District have been able to create teaching materials based on Jayapura Ethnoscience that can be used in science teaching in schools and c) The interest of science teachers in Muara Tami Jayapura District is enthusiastic in participating in training activities, which is shown by their active asking questions and having discussions both with fellow training participants and with resource persons.